Evidence generation for sustained impact in the response to gender-based violence: lessons from the SRHR Africa Trust Zimbabwe - Mazhambe, Raymond; Mushunje, Mildred (Frontiers in Global Women's Health, 2023)
Gender-based violence (GBV) is a pervasive problem in Zimbabwe, affecting women and girls. Types of GBV prevalent in Zimbabwe include sexual violence, intimate partner violence (IPV) and child marriages. Issues of evidence generation remains crucial in the development of interventions tailor made to the GBV response. In a bid to build pathways for strengthening GBV programming and for influencing policy change, SRHR Africa Trust (SAT) Zimbabwe conducted a secondary data review for GBV cases between 2018 -2019 in collaboration with the Zimbabwe Republic Police (Victim Friendly Unit) to understand the driving factors and incidences of GBV in Zimbabwe, context specific information with regards to sexual violence and an overview of the perpetrator types. The study proffered recommendations that focus on the importance of improving GBV reporting and programming in Zimbabwe. The study established that some of the driving factors for physical violence include poverty, infidelity, alcohol and drug abuse and that sexual violence occurs through intimate partners and close relatives among other factors.